(3QSGdI CjgG GdhdOs - (3eMeO Hf eMeO Hf eMeO GdZRGdj GdTGaYj GdWhSj , CHh MGeO, MLI GdGSdGe GdZRGdj,J (B505 (3g` s ((3YeQ Hf eQGO GdbGVi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hGdYGbHI ddeJbjf EYde Cf hGMOkG ef GdWdHI GdeJbOejf dGRe NOeI GdTjN GdZRGdi EYde CjgG GdhdO GdYRjR GdfUjMI Sgd hGdeTcd bHhdgG s
(3BNQgG (B:s
(3CjgG GdhdO Cfi cJHJ ai gPG ai gPG GdaUd ajfHZi dc Cf JYed eG ajgG hdG JfSGfi ajg ef GdOYGA dG Edg EdG CfJ SHMGfc Efi cfJ ef GdXGdejf s
(3HgG fXGe GdJYbjHIs
(3HBNQgG EVGaGJ ddeDdas
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B266 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B79s
Keywords: (3GdadSaI hGdefWbs